2015
DOI: 10.1002/art.39000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnetic Resonance Imaging–Detected Tenosynovitis in the Hand and Wrist in Early Arthritis

Abstract: Objective. Magnetic resonance imaging (MRI) is a sensitive method to detect inflammation in rheumatoid arthritis (RA), visualizing synovitis, bone marrow edema, and tenosynovitis. The prevalence of MRIdetected tenosynovitis and its diagnostic value in early arthritis are unclear. This study was undertaken to identify the frequency of MRI-detectable tenosynovitis at the metacarpophalangeal (MCP) and wrist joints in early arthritis and the association of these with RA and the severity of RA.Methods. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 18 publications
4
40
0
Order By: Relevance
“…In a recent study, however, MRI-detected tenosynovitis was noted to be a common finding in early arthritis 25. Further investigations in this regard may be warranted.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study, however, MRI-detected tenosynovitis was noted to be a common finding in early arthritis 25. Further investigations in this regard may be warranted.…”
Section: Discussionmentioning
confidence: 88%
“…MRI-detected bone marrow oedema and osteitis are independent predictors of radiographic progression in early RA,23 24 but data are limited in early arthritis. Finally, two recent studies have shown that hand flexor or extensor tenosynovitis on US36 or MRI25 may be a specific—although not very sensitive—marker for RA classification.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies evaluated mainly MRI (three studies35 49 50) (see online supplementary materials S5). Other imaging modalities were US (one study51) and bone densitometry (BMD) performed on hand X-rays (one study52).…”
Section: Resultsmentioning
confidence: 99%